A household survey: unintentional injury frequency and related factors among children under five years in Malatya - Atak, Nazli; Karaoğlu, Leyla; Korkmaz, Yasemin; Usubütün, Seda (The Turkish Journal of Pediatrics, 2010)
Accidents constitute a major public health problem around the world. They are one of the leading causes of death among children under five, with residential accidents accounting for the majority. Since there is no recording system that provides routine and reliable data about accidents, the data about the frequency of accidents and related factors are available only through researches. The aim of this study was to determine the frequency of injury-producing accidents and related factors among children aged under five who live in Malatya city center. In this cross-sectional epidemiological study, we covered first each regional health center in Malatya city center, a total of 30 clusters out of the population using a proportional systematic sampling method, and in turn, a sample size of 704 children under five. The frequency of injury-producing accidents was determined as 12.6%. The majority of the accidents occurred in the house, and 65.3% of them were due to falls; in 65.1%, accidents occurred in the presence of the mother. The frequency of the accidents was highest for the 4-5 age group (14.1%) and lowest among those < or = 1 year. It was found that maternal age < or = 30 (odds ratio [OR] = 1.9) and patient age of 4-5 years (OR = 5.4) primarily affected the chances of having an accident. A drawing of a kitchen setting, representing a total of 13 accident-producing risks, was given to the mothers, who were able to define an average of only 5.1 +/- 0.2 risks. The average number of risks defined by the mothers was found to be associated with the age of the child, educational background of the mother, her occupation, type of family, and monthly family income. No relation was determined between the accident risk awareness and accident frequency. In conclusion, the injury-producing accident frequency among children aged under five in central Malatya was found to be high. Given the finding that children have accidents in the presence of their mothers, it seems reasonable to provide mothers with parenting applications and training programs to reduce the home-based risks.